Enhancing SAR Satellite Constellation Efficiency Through NATS-Enabled Inter-Satellite Communication - Bin Abid, Emad (My University, 2026)
This thesis investigates the feasibility and benefits of inter-satellite communication within a small satellite constellation by developing a proof-of-concept implementation using the Flight Software (FSW) Application Protocol over NATS messaging on top of TCP/IP. The work abstracts away the physical inter-satellite communication layer - such as radio frequency or optical links - and instead assumes the existence of an intermittent IP-based network, where TCP connections between satellites can be established sporadically. This assumption reflects a realistic and reproducible laboratory environment using flatsats. The primary objective is to evaluate the applicability of software-defined messaging infrastructure in a space-relevant context, with a focus on demonstrating key operational use cases. These include: coordinating imaging tasks across satellites; relaying large data objects from satellites lacking ground connectivity; enabling data uploads from ground to orbit via intermediate satellites; and maintaining synchronized state across nodes through NATS JetStream stream replication. The system is implemented in Golang, with NATS providing the messaging layer to facilitate resilient and asynchronous communication under constrained and unreliable network conditions. Through controlled testing, the study assesses performance indicators such as message delivery reliability, latency, data throughput, and the robustness of stream synchronization mechanisms. The results illustrate the potential of lightweight, application-layer protocols to support distributed coordination in satellite constellations, contributing to the broader field of software-defined space systems and laying groundwork for future inter-satellite networking architectures. Keywords: Inter-satellite communication, Flight Software (FSW) Application Protocol, NATS messaging, Satellite constellation, Software-defined space systems
Keywords: Inter-satellite communication, Flight Software (FSW) Application Protocol, NATS messaging, Satellite constellation, Software-defined space systems